Pelanggaran Prinsip Kesantunan dalam Video “GURU” - Alit Mahendra, Gusti; Madia, I Made (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2020)
This research was conducted aiming to explain the forms of language impoliteness used by daughter against fathers. Speech that contains elements of politeness in language is the main object in this research. "Violation of the Principle of Politeness in the 'Guru' Video" aims to analyze the utterances on violations of the politeness principle of language in the video titled "Guru". This study uses qualitative descriptive research methods. Data collection using the refer method with the ability to engage in competent free listening then proceed with the note taking technique. The data in this study are in the form of phrases, clauses, and sentences in dialogues on "Guru" video. Based on the results, most violation data are violations of the maxims wisdom amounted 3 utterances, followed by maxim of silence feeling of 2 utterances. Implications that appears in the video "Guru" there are 6 implicature where 3 forced implicature, honestly admitted of 2 implicature and 1 admitted implicature. Impoliteness speech is dominated by daughter as speakers. This research is also expected to be an input for Balinese language teachers so that the community and school environment can apply politeness in speaking.